Introduction to the physics of the cryosphere - Sandells, Melody; Flocco, Daniela (IOP (Series). Release 22., 2022)
This second edition defines different parts of the cryosphere including: permafrost, snow, land ice, sea ice, ocean, atmosphere and covers numerical modelling of thermodynamic exchanges: conservation of mass, energy, and momentum.